2021
DOI: 10.1108/ijshe-09-2020-0335
|View full text |Cite
|
Sign up to set email alerts
|

Plant blindness and sustainability

Abstract: Purpose The present paper aims to examine the concept of “plant blindness” in the context of current sustainability debates. “Plant blindness” was the term introduced in 1999 by the botanists and educators James H Wandersee and Elisabeth E Schussler to describe what they saw as a pervasive insensitivity to the green environment and a general neglect of plants on the part of biology education. Design/methodology/approach The fundamental importance of plants for life on Earth and the socio-educational challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 81 publications
(74 reference statements)
1
28
0
2
Order By: Relevance
“…These results are in line with other research which concluded that MS is important in accepting and using technology (Gagne et al, 2000). Previous research by Jose et al (2019), Thomas et al (2021), and Uno (2009) indicates that in the prevention of plant blindness in students, cooperation between teachers, botanists, educational policymakers, and school management is very important. The results of our research indicate that teachers' decisions in relation to CI for using DIKs is most obviously influenced by the recognition of their efforts in using these teaching tools on the part of educational inspectors.…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with other research which concluded that MS is important in accepting and using technology (Gagne et al, 2000). Previous research by Jose et al (2019), Thomas et al (2021), and Uno (2009) indicates that in the prevention of plant blindness in students, cooperation between teachers, botanists, educational policymakers, and school management is very important. The results of our research indicate that teachers' decisions in relation to CI for using DIKs is most obviously influenced by the recognition of their efforts in using these teaching tools on the part of educational inspectors.…”
Section: Discussionsupporting
confidence: 90%
“…The students are drawn to plants for different reasons; there is the "need for knowledge" in relation to wanting to know more, but also awe towards plants (Sanders, 2004;Nyberg & Sanders, 2014;Nyberg, 2017), their function for society (Pany, 2014) or ecosystems Thomas, Ougham & Sanders, 2021). The students when noticing a plant, want to know "here and now" what they are looking at, but also possible genetic connections between different plants, the biological life of the plants and how the plants are used or affected by humans.…”
Section: Discussionmentioning
confidence: 99%
“…This research is thus a response to Sanders' ( 2007) call for more research on teachers' and learners' perceptions of plants. It is also a contribution to biology and environmental didactics and thereby a response to Thomas, Ougham and Sanders (2021), who in their examination of the concept of plant blindness conclude that education is essential and that the training of teachers is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study is to examine the characteristics of plant awareness disparity and human–plant relations in a broad literature base, encompassing both the educational and ethnobiological literature. Other studies have reviewed the educational literature on plant blindness in the context of sustainability education (Amprazis & Papadopoulou, 2020; Thomas et al, 2021) but did not extend to other fields of social research. Balding and Williams (2016) considered ethnobiological studies in their essay about plant blindness in biodiversity conservation but did not undertake a full review.…”
Section: Introductionmentioning
confidence: 99%